Kuliah Kerja Nyata: Strategi Pemberdayaan UMKM melalui Inovasi Produk Rumah Tangga dan Pelatihan Kecantikan - Khairina Tambunan; Chadiza Auliana Utami; Nasyah Aurin; Tasya Agustina Wahidha; Ganis Filma Afilika (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The Community Service Program (Kuliah Kerja Nyata, KKN) is a form of student engagement in society that plays a crucial role in bridging academic knowledge with practical needs in the field. This article discusses strategies for empowering Micro, Small, and Medium Enterprises (MSMEs) through KKN activities carried out in Desa Sei Mencirim, Kecamatan Sunggal, Kabupaten Deli Serdang. The empowerment program focuses on two main areas: household product innovation and beauty skill training. In terms of product innovation, students collaborated with the local community to produce the “Beningku” dishwashing soap, which requires minimal capital, involves a simple production process, yet holds significant economic value. The product received a positive response from housewives, as it can be used for personal needs or resold as an additional business opportunity. This approach provides the community with new insights on transforming simple materials into valuable products, while fostering local creativity and innovation. On the other hand, in the service skills domain, a beauty class in collaboration with the Mizzu brand provided makeup training for teenage girls and housewives. The training not only enhanced technical skills in makeup application but also encouraged participants to start local makeup service businesses. This activity promotes entrepreneurship and self-reliance while expanding skills that can be applied in daily life or as an additional source of income. The results indicate a significant increase in knowledge, skills, and entrepreneurial motivation among community members. In addition to providing economic benefits through new business opportunities, the KKN activities also strengthened community confidence, participation, and social solidarity. Through a participatory approach, KKN has proven to be an effective strategy in empowering village MSMEs by utilizing local potential and simple innovations, supporting not only economic growth but also enhancing social capacity and community competencies.